Asian development : - James, William E. (University of Wisconsin Press, 1989)
While the world’s attention has been focused on the spectacular economic success of Japan and Korea, the less developed countries of Asia have often been neglected. Asian Development closes the gap. In nontechnical style and with minimal mathematics, it presents an in-depth perspective on the economic development of fourteen countries in East, Southeast, and South Asia.